2020
DOI: 10.3390/nano10102065
|View full text |Cite
|
Sign up to set email alerts
|

Are Titania Photocatalysts and Titanium Implants Safe? Review on the Toxicity of Titanium Compounds

Abstract: Titanium and its compounds are broadly used in both industrial and domestic products, including jet engines, missiles, prostheses, implants, pigments, cosmetics, food, and photocatalysts for environmental purification and solar energy conversion. Although titanium/titania-containing materials are usually safe for human, animals and environment, increasing concerns on their negative impacts have been postulated. Accordingly, this review covers current knowledge on the toxicity of titania and titanium, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 219 publications
(338 reference statements)
0
31
0
Order By: Relevance
“…Although titanium has already been used for several purposes [ 27 ], the toxicity of this metal has not been addressed in detail, considering the direct and indirect consequences and acute and chronic toxicity [ 28 ]. In the present study, no cell cytotoxicity was found after 24 h in nanotube titanium sheets (100 nm and 150 nm) showing potential biocompatibility, which is a favorable property for osseintegration.…”
Section: Discussionmentioning
confidence: 99%
“…Although titanium has already been used for several purposes [ 27 ], the toxicity of this metal has not been addressed in detail, considering the direct and indirect consequences and acute and chronic toxicity [ 28 ]. In the present study, no cell cytotoxicity was found after 24 h in nanotube titanium sheets (100 nm and 150 nm) showing potential biocompatibility, which is a favorable property for osseintegration.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria corrosion on implants is due to biofilm formation, under which the interfacial electrochemical processes start and are followed by microbially-influenced corrosion on substratum metals and alloys [ 19 , 20 ]. Corrosion is a complex process mediated by interaction occurring between anaerobic and aerobic bacteria [ 7 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of aeration in these areas helps create an anode where corrosion can occur by releasing metal ions into the saliva. Moreover, by combining the released metal ions with the saliva’s chloride ions or the bacteria’s end-products, more reactive species will be generated, and the metal will be corroded further [ 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Titanium alloys are currently the standard in craniomaxillofacial surgery. Alloys grade 5 or 23 are mainly used, but they are not ideal implantation materials for humans [ 20 ]. Titanium alloy is implanted into the bone; after some time, it passes into the surrounding soft tissues and reaches high concentrations there.…”
Section: Discussionmentioning
confidence: 99%